Konsep Pertanggungjawaban Penggunaan Dana Penjaminan Pemulihan Lingkungan Hidup Oleh Pemerintah dan Pelaku Usaha dan/atau Kegiatan - Sisma, Annisa Fianni; Subekti, Rahayu (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Accountability for the use of environmental recovery guarantee funds by the government and business actors/activities is an important issue in environmental protection and recovery efforts. This guarantee fund is intended to support the implementation of environmental recovery and rehabilitation activities generated by business actors/activities. However, there are concerns regarding the effectiveness, accountability, and transparency in the use of these funds. Therefore, it is necessary to examine there is an accountability mechanism for accountability and technical use of these funds in Indonesia or not. The research aims to analyze the concept of liability related to the use of environmental recovery guarantee funds. This research is a legal research with a statutory approach. The results show that the amount of guarantee funds for the restoration of environmental functions is difficult to determine because it may only be seen for a long time and it is difficult to determine the parameters of its economic value. Accountability and technical use of these funds have not been regulated in Indonesia. In fact, one of the objectives of knowing the mechanism for using guarantee funds for the restoration of environmental functions is the fulfillment of the principle of accountability in organizing the state in accordance with the General Principles of Good Government. In addition, the nominal amount should be conveyed transparently to the public. Then, the technical implementation of overcoming environmental pollution and/or damage, and/or restoring functions with these funds cannot be monitored because it is not published. In fact, the public has the right to play an active role in environmental protection and management and obtain information related to the environment. Regulations regarding this matter can be applied to the Environmental Information System that can be accessed online by the public which contains the nominal amount, technical accountability, and mechanism for using guarantee funds for the restoration of environmental functions.